The Structural RelationshipAnalysis between Innovation and Export Performance of Food Industries, Thailand - Pattarapon Chummee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Export performance is very important for the development of the country. Can Concluded that exports promote growth, economic growth rate and domestic income. However, exports need innovation. The purpose of this research was to study the causal influence of innovation and export capacity. Contains innovative theory of entrepreneurship. export behavior theory and competitive advantage theory and conducting a literature review according to the research conceptual framework. The objective of this is the study the casual relation between innovation and export performance. The sample group used in the study was 400 SMEs in food business in Thailand. Research result found that organizational innovation had a positive direct correlation with export performance (t=6.47), marketing innovation was also found to have a positive direct correlation with export performance (t=6.74). At least, the process innovation was directly positively correlated with statistically significant (t=14.04) with export performance. when assessing the fit index found that the valuable Chi-square=248.13 , df=222, chi-square/df=1.11, RMSEA=0.055 can be concluded that there is a good consensus. Recommendations developing innovations suitable for small and medium-sized enterprises in Thailand by increasing marketing innovation including various innovations suitable for every production and export process Connecting entrepreneurs to social media to reach global consumers It can be said that entrepreneurs must add new innovations that can create additional value, such as history. Various stories in the product Moreover, the same product should not be produced repeatedly, it should be unique to each locality. Create packaging that looks good and is environmentally friendly.